Stability analysis of rock slopes using the interface contact model and strength reduction method - Yang, Rui; Li, JiaCheng; Bai, Xue; Zeng, Cheng (Frontiers in Earth Science, 2023)
The assessment of rock slope stability is usually controlled by the presence of discontinuities. The block theory is an established method in practical engineering to predict the stability of rock slopes. A maximum of two discontinuity planes are considered in the application of the block theory. It would lead to inaccurate prediction of slopes with multiple discontinuity planes. A novel method for estimating the safety margin of rock slopes is proposed, which is capable of considering the contribution of all discontinuities to the stability problem. The discontinuity planes are simulated by an interface contact model within the theoretical framework of the finite difference method. The factor of safety is obtained by the strength reduction method. The failure criteria of rock slopes are also discussed. The proposed model can simulate discontinuous planes in a more realistic manner and thus is more effective in engineering practice. To demonstrate the effectiveness of the proposed model, several numerical examples are presented, which showcase its superiority for predicting the stability of blocks composed of multiple discontinuities. Several numerical examples are analyzed to confirm the effectiveness of the proposed model and its superiority in stability prediction of blocks formed by multiple discontinuities.